Effects of Modified Nano-SiO2 Particles on Properties of High-Performance Cement-Based Composites - Zhidan Rong (Materials, 2020)
In this research, silane coupling agent was used to modify the surface of nano-SiO2, particles and the effects of modified nano-SiO2 particles on the mechanical properties of high-performance cement-based composites and its mechanism were systematically studied. The results indicated that the optimum modification parameters were a coupling agent content of 10%, reaction temperature of 65 °C, and reaction time of 8 h. Compared with the unmodified nano-SiO2, the modified nano-SiO2 promoted and accelerated the hydration process of cement. The pozzolanic effect, filling effect, and nucleation effect of modified nano-SiO2 made the microstructure of the composite more compact, and thus improved static mechanical properties of cement-based composites.